Sentido común "común" y sentido común "sensato". Una reivindicación de Thomas Reid - José Hernández Prado (Tópicos, 2013)
This article attempts to show that Thomas Reid (1710-1796) specially argued not a "common" common sense, but a "sensible" one. In addition, it proposes that Reid's philosophy of common sense is quite important amongst those of its kind.